Microstrip Array Antenna using Series-Corporate Feed for Navigation System - Taher Khalifa; N. Ramli; N.M. Sahar (IAES Indonesian Section, 2020)
In this paper, the proposed antenna consists of a single transmission line for 6-elements microstrip array antenna using Rogers RT5880 substrate material with a dielectric constant (εr) of 2.2 and thickness of 0.787 mm for navigation applications. The array structures of unequal patches placement are proposed with corporate feed line and H-shaped configurations are employed on the substrate and used the microstrip feed line with a corporate feed network excited via 50 Ω with T-junction method to control the feed for each group. 6-elements microstrip array antenna has operated at the resonant frequency of 1.27 GHz was obtained between the frequency from 1.2663 GHz to 1.2734 GHz where the S11-parameters of the structure designed and simulation below than <-10 dB. The analysis shows the antenna gain has increased 72.6% with high directivity as compared to single elements microstrip antenna. The radiation characteristics and other array parameters are evaluated with respect to the application requirements. However, circular polarization has obtained in 6-elements array antenna as the axial ratio is successfully achieved below than -3dB. The antenna efficiency, the current distribution, VSWR, and S11-parameters of the proposed 6-elements CP microstrip array antenna have been presented and discussed in detail. The design methodology and the measurement results have been presented and discussed in this paper.